Solutions to Boundary Value Problem of Nonlinear Impulsive Differential Equation of Fractional Order (Communications in Mathematical Research, 2021)
This paper is devoted to studying the existence and uniqueness of solutions toa boundary value problem of nonlinear fractional differential equation with impulsiveeffects. The arguments are based upon Schauder and Banach fixed-point theorems.We improve and generalize the results presented in [B. Ahmad, S. Sivasundaram,Existence results for nonlinear impulsive hybrid boundary value problems involvingfractional differential equations, Nonlinear Analysis: Hybrid Systems, 3(2009), 251–258].